C37-38 alkenone core top data and downcore alkenone pilot samples from the Indo-Pacific Warm Pool - Joseph B Novak; Sarah McGrath; Karen Wang; Sian Lao; Steven C Clemens; Wolfgang Kuhnt; Yongsong Huang (PANGAEA, 2022)
Alkenone core top data (UK extquotesingle37, UK extquotesingle38ME, UK extquotesingle38ET, UE extquotesingle36OME, K38ME/K37, K37/K38) from 168 samples that span a geographic region from from 76.75°N -76.5°S and 178.8E-179.6W. Data were collected for calibration of alkenone indices to sea surface temperature. Also included are alkenone data (UK extquotesingle37, UK extquotesingle38ME, and SST estimates) from 12 early Pliocene age samples from ODP sites 1143 and 806, which were collected to constrain the behavior of UK extquotesingle38ME relative to UK extquotesingle37 at warmer than modern ocean SSTs. Data were collected via gas chromatography-flame ionization detection Agilent 214 7890N Series instrument with splitless injection and Restek Rtx-200 ms (105 m x 250 μm x 0.25 x 215 μm) poly(triflouropropylmethylsiloxane) stationary phase semi-polar column.